Les Institutions astronomiques - Mesmes, Jean Pierre de 1516-1578 (Paris de Vascosan, 1557)
'Les Institutions astronomiques' is the first scientific work of the poet and scholar Jean-Pierre de Mesmes (1516-1578). It is also the first book on astronomy to be written in French instead of Greek and Latin. This publication had two objectives: to boost the knowledge of the exact sciences (and to make up for the backwardness in that area in France) and to enrich the French language, enhancing its value and prestige. The book also provides an of introduction to the practice of astronomy: how to predict the characteristics, time and duration of an eclipse with the help of the tables, how to modify the data of the Ephemerides by taking into account the different longitudes etc. It also shows how to carry out a few simple observations, such as finding the stars that mark the equator, or locating the four cardinal points. The author uses concrete examples, very clear figures and precise drawings. It is therefore a useful and complete book, open to both the theoretical and practical aspects of astronomy.
contenant les principaux fondemens et premieres causes de cours de mouvemens celestes. Avec la totale revolutions du ciel & de ses parties: ses causes & raisons de eclipses, tant de la lune, que du soleil.
Keywords: 16th Century (1501-1600); Method; Astronomy; French; Paris (France)